Recent Progress in Accessing Multi-functionalized Caged Hydrocarbons: En Route to Highly Functionalized Saturated (Bio)isosteres of Benzene Rings - Nagasawa, Shota; Iwabuchi, Yoshiharu (Synthesis, 2024)
Recently, many saturated bioisosteres of the benzene ring have been developed, and their applications in drug development have been evaluated. Most of these bioisosteres are caged hydrocarbons, which have rigid skeletons and three-dimensional spaces. Recent efforts to synthesize these caged hydrocarbons have enabled access to multi-functionalized congeners that are expected to be (bio)isosteres of multi-functionalized benzenes. This short review summarizes recently reported methods for obtaining multi-functionalized (typically more than disubstituted) caged hydrocarbons.1 Introduction2 Proposed Structures of Caged Hydrocarbons as Saturated (Bio)isosteres of the Benzene Ring: A Brief Summary3 Access to Multi-functionalized Caged Hydrocarbons: De Novo Synthetic Approaches3.1 Bicyclo[1.1.1]pentanes (BCPs)3.2 Bicyclo[2.1.1]hexanes (BCHs)3.3 Bicyclo[3.1.1]heptanes (BCHeps)3.4 Others4 Access to Multi-functionalized Caged Hydrocarbons: C–H Functionalization5 Conclusion
Keywords: bioisostere; caged hydrocarbons; de novo synthesis; C–H functionalization; radical functionalization